Identification of Loading and Unlocking Process Time at Denpasar Goods Terminal - Dynes Rizky Navianti; Putu Ayu Govika Krisna Dewi; Stefanus Sylvan Ryanto (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2023)
One of the goals of a company organization is to minimize production costs to obtain a guarantee of survival. The creation of a production company (both goods and services) requires qualified and competent human resources. In a production system, there is an inventory or inventory process. Inventory is an effort to anticipate stock due to high demand from consumers. This is due to the delay in the goods. In an inventory process, there are two processes, namely loading (loading process) and unloading (unloading process). In the process of inventory loading and unloading, there is a problem, namely the inefficiency of time. These problems disrupt and hinder the product distribution process which has implications for wasting time. However, in this study related factors have been identified that affect loading and unloading processing time. The result is that the fatigue variable and the driver psychology variable do not significantly influence the loading and unloading processing time. Simultaneous or joint significance test, has a probability/significance value of the F test of 0.150087 with a significance level of 0.05